Antioxidant profiles of a prepared extract of Chinese herbs for the treatment of atopic eczema - Chung, L.Y. (2008)
A standardized mixture of Chinese herbs, Zemaphyte((R)) taken orally as a daily decoction has been shown to be effective in the treatment of atopic eczema. This study showed that Zemaphyte((R)) is an efficient antioxidant, being capable of scavenging both superoxide and hydroxyl, and preventing peroxidation of biological membranes. It does not degrade hydrogen peroxide directly, but instead most likely forms a Zemaphyte-hydrogen peroxide complex. The complexed hydrogen peroxide can then be degraded in the presence of catalase to form oxygen and water. It is conceivable that Zemaphyte((R)) may contribute to the down-regulation of the activities of cells implicated in atopic eczema through its antioxidant activities. Copyright (c) 2008 John Wiley & Sons, Ltd.